The Impact of Computational Thinking Pillars on the Development of BNCC Competencies through the Micro:bit - Osorio, Alma G. Villamediana; Cabreira, Tauã Milech (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2024)
This article examines how the pillars of computational thinking - decomposition, pattern recognition, abstraction, and algorithms - support the development of skills outlined in Brazil's National Common Curricular Base (BNCC) for grades 6th to 9th. The study analyzes the alignment between computational thinking pillars and BNCC competencies across various subjects of the final years of elementary school, and lays the groundwork for future integration of practical micro:bit projects to work with both, aiming to enhance students' cognitive, socio-emotional, and technological skills, while strengthening pedagogical practices in line with BNCC standards.